PERSEPSI MASYARAKAT TERHADAP PENERAPAN SMART PLUG WIFI DALAM EFISIENSI ENERGI LAMPU JALAN DI KECAMATAN SELEBAR - Wijaksono, Indra; Jamhari, Djauhar; Dimas, Fatwa; Geaparga, Genny; Rizqo, Imam; Hamdi, Muhammad; Dewi, Mutiara; Ferdiansyah, Supardi (Education and Talent Development Center of Indonesia, 2025)
Smart Plug Wifi, an Internet of Things (IoT) innovation, has strong potential to improve energy efficiency of public street lighting. Its success, however, is contingent upon local community perceptions and acceptance. This study aims to analyze the public’s perception in Selebar Subdistrict toward the deployment of Smart Plug Wifi for streetlight energy efficiency and to identify key drivers and barriers based on the Technology Acceptance Model (TAM). A descriptive qualitative approach was employed with 30 purposively sampled respondents spanning three age groups (18–30; 31–50; >50 years) and diverse occupations. Data were collected through semi-structured interviews and thematically analyzed across TAM dimensions: perceived usefulness, perceived ease of use, and attitude toward the technology. Results indicate that 60% of respondents view Smart Plug Wifi as an effective solution for reducing electricity consumption evidenced by their appreciation of precise on–off scheduling while 30% remain neutral and 10% reject the technology due to cost concerns. Primary drivers include environmental awareness and trust in government policy, whereas major barriers are limited socialization and technical understanding. These findings underscore the necessity for more robust communication strategies and technical training to foster wider adoption. This study contributes to the Smart City and public energy efficiency literature by providing empirical insights into user acceptance of IoT devices in public spaces and offers practical policy recommendations for local governments to design inclusive smart lighting programs.